Primary Care Procedures in Women's Health - Sulik, Sandra M.; Heath, Cathryn B.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2010)
There are many reasons for primary care providers to offer women s health procedures in an office setting, from the value patients place on continuity of care to the lack of access to specialty care that patients may experience in rural areas. Primary Care Procedures in Women s Health has been designed to introduce simple office procedures to clinicians, as well as office staff who must familiarize themselves with new equipment and new billing and coding information. Each chapter in this book is written by a primary care physician and outlines one women s health procedure and its background information, indications, contraindications, complications, equipment, procedure steps, an office note, patient instructions and a patient handout. Tricks, helpful hints, algorithms and a wealth of illustrations are included through the book. Primary Care Procedures in Women s Health is a manual that will allow all providers including family physicians, general internists, residence, nurse practitioners, nurse midwives and physicians assistants to be competent and comfortable performing a spectrum of office-based procedures.
Introduction: The Case for Procedures in Primary Care -- Coding, Billing, and Reimbursement for Procedures -- Legal Aspects of Office-Based Women s Health Procedures -- Empathic Pelvic Examination -- Difficult Exams: Cystocele, Rectocele, Stenotic Cervix/Cervical Dilatation, Nonsexually Active Women, Elderly Women -- Sexual Assault Victim Examination -- Pap Smear -- Vaginal Discharge -- Cervical Polyp Removal -- Diaphragm and Cervical Cap -- Copper Intrauterine Device -- Levonorgestrel Intrauterine System Insertion -- Intrauterine Device Removal -- Natural Family Planning -- Implanon®: Insertion and Removal -- Pessary -- Bartholin Gland Cysts and Abscesses -- Endometrial Biopsy -- Breast Cyst Aspiration -- Vulvar Skin Biopsy -- Treatment of Genital Warts -- Colposcopy -- Cervical Cryotherapy -- LEEP: Loop Electrosurgical Excision Procedure -- Hysterosalpingography/Hysterosalpingogram (HSG) -- Medication Abortion Using Mifepristone and Misoprostol -- Manual Vacuum Aspiration (MVA) Abortion -- Botulinum Toxin A Injections for Reduction of Facial Rhytids -- The Use of Cosmetic Lasers in Clinical Practice -- Glycolic Peels.
Keywords: Medicine; Family medicine; Gynecology; Internal medicine; Emergency medicine; Medicine & Public Health; Primary Care Medicine; General Practice / Family Medicine; Internal Medicine; Gynecology